THE INFLUENCE OF SOCIAL MEDIA ON THE CONSTRUCTION OF IDENTITY AND SOCIAL BEHAVIOR IN YOUTH (CIPEEX, 2025)
This study examines the influence of social media on the construction of identity and social behavior in youth, integrating perspectives from psychology and sociology. The methodology adopted is theoretical, based on a literature review of key works, including authors such as Goffman (1959), Turkle (2011), boyd (2014), and Twenge (2017), who discuss the impact of technology on social life and the dynamics of privacy and exposure in social networks. The results indicate that social media serves as a space where young people construct and explore different aspects of their identity. However, the constant exposure to idealized standards and the pursuit of social approval can lead to a distorted self-image and emotional issues such as anxiety and depression. These findings are consistent with Twenge's (2017) studies, which associate intensive social media use with negative psychological effects, particularly among adolescents and young adults. In conclusion, while social media offers significant opportunities for identity construction and social interaction, it is crucial to promote a balanced and conscious use of these platforms. Educational interventions that encourage critical reflection on social media use are essential to help young people benefit from these tools without succumbing to the negative pressures they can generate.
Keywords: identity; social media; social behavior